Modulation by luminal factors on the functions and migration of intestinal innate immunity - Higashiyama, Masaaki; Miura, Soichiro; Hokari, Ryota (Frontiers in Immunology, 2023)
Luminal antigens, nutrients, metabolites from commensal bacteria, bile acids, or neuropeptides influence the function and trafficking of immune cells in the intestine. Among the immune cells in the gut, innate lymphoid cells, including macrophages, neutrophils, dendritic cells, mast cells, and innate lymphoid cells, play an important role for the maintenance of intestinal homeostasis through a rapid immune response to luminal pathogens. These innate cells are influenced by several luminal factors, possibly leading to dysregulated gut immunity and intestinal disorders such as inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), and intestinal allergy. Luminal factors are sensed by distinct neuro-immune cell units, which also have a strong impact on immunoregulation of the gut. Immune cell trafficking from the blood stream through the lymphatic organ to lymphatics, an essential function for immune responses, is also modulated by luminal factors. This mini-review examines knowledge of luminal and neural factors that regulate and modulate response and migration of leukocytes including innate immune cells, some of which are clinically associated with pathological intestinal inflammation.